Use of caffeine as an indicator of pollution by domestic sewage in urban water bodies - Bega, Joao Miguel Merces [UNESP]; Oliveira, Jefferson Nascimento de [UNESP]; Albertin, Liliane Lazzari [UNESP]; Isique, William Deodato [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2021)
In population centers, aquatic environments are in constant degradation due to the activities carried out in watersheds, with the release of domestic sewage being one of the biggest sources of pollution. Environmental monitoring of water quality reflects the inputs generated in the areas of influence and gives evidence of likely origins. However, it is the substances for exclusively anthropic use that can prove the existence of the release of such polluting loads. In this context, the present study aimed to evaluate the efficiency of caffeine as an indicator of pollution by domestic sewage. The analytical method used for its identification was high-performance liquid chromatography (HPLC). In order to relate the results obtained for caffeine with the dilution and nonpoint sources pollution, data on precipitation, dissolved oxygen, and biochemical oxygen demand were also measured. Caffeine was found in all samples analyzed, with concentrations ranging from 0.01 to 7.80 mg.L-1. The highest values were observed in the rainy season, related to the overflow and leakage of domestic sewage. This study infered the use of caffeine as an efficient indicator of pollution by domestic sewage.
Keywords: emerging compounds; environmental degradation; nonpoint source pollution; urban areas